2021
DOI: 10.21203/rs.3.rs-926816/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Obesity And Its Related Factors Among University Medical Students In Syria: A Cross- Sectional Study

Abstract: Background: Obesity is a world-wide pandemic that has many contributing factors. Healthcare personnel has a crucial role in health promotion and is considered the role models for the general population. We aim to evaluate the BMI and physical activity (PA) of medical students their association with multiple variables, including psychological.Methods: This is a cross-sectional study that was conducted in Damascus University. Paper-based questionnaires were distributed that included International PA Questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In their study in Southern Italy, [26] found that 62.6% of respondents were physically insufficient (Inactive). Another study by [27] reported a higher prevalence (36.5%) of moderate and high physical activity among Damascus university students. In the high activity category, about 73.2% were males.…”
Section: Physical Activity Among University Studentsmentioning
confidence: 90%
“…In their study in Southern Italy, [26] found that 62.6% of respondents were physically insufficient (Inactive). Another study by [27] reported a higher prevalence (36.5%) of moderate and high physical activity among Damascus university students. In the high activity category, about 73.2% were males.…”
Section: Physical Activity Among University Studentsmentioning
confidence: 90%